Inside Cover: Red Blood Cells Polarize Green Laser Light Revealing Hemoglobin′s Enhanced Non‐Fundamental Raman Modes (ChemPhysChem 18/2014). Issue 18 (15th December 2014) - Marzec, Katarzyna M.; Perez‐Guaita, David; de Veij, Marleen; McNaughton, Don; Baranska, Malgorzata; Dixon, Matthew W. A.; Tilley, Leann; Wood, Bayden R.
<x xml:space="preserve">Abstract</x> Red blood cells (RBCs) and solid‐state hemes give rise to intense overtone bands when excited with green laser light. On p. 3963, B. R. Wood et al. demonstrate that combining the non‐fundamental and fundamental regions of the resonance Raman spectrum improves the sensitivity and diagnostic capability of the technique.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>